Ready, Willing and Able? An Investigation of the Theory of Planned Behaviour in Help-Seeking for a Community Sample with Current Untreated Depressive Symptoms - Tomczyk, S. (Prev Sci, 2020)
Applying health behaviour change models, such as the theory of planned behaviour (TPB), to help-seeking for mental health problems can address the deficit in health care utilisation. However, previous studies largely focused on help-seeking intentions and not behaviour, which might be problematic due to the intention-behaviour gap. Hence, TPB and help-seeking were examined in a German community sample with current untreated depressive symptoms: 188 adults (M(age) = 50.34; SD = 16.19; 70.7% female) participated in a baseline interview and survey measuring components of the TPB (attitudes, subjective norms and perceived behavioural control) and help-seeking intentions. They reported actual help-seeking from mental health professionals via telephone surveys 3 and 6 months later. To better understand the potential gap between help-seeking intentions and behaviour and to investigate the contributions of readiness, willingness and ability to seek help, two path models were constructed in accordance with the TPB controlling for covariates. Attitudes (β = .24), subjective norms (β = .25) and self-efficacy (β = .15) were significantly associated with intentions (R(2) = 26%), which predicted help-seeking (Cox and Snell’s pseudo-R(2) = 23%); controllability did not predict help-seeking. In sum, the TPB provides a reliable framework to explore help-seeking behaviour for mental health problems. Based on these findings, prevention efforts should focus on readiness and willingness to seek help (e.g. foster positive attitudes and social support of treatment). However, the role of ability, operationalised as perceived behavioural control and (perceived) barriers to help-seeking, warrants further research, as self-efficacy but not controllability was associated with help-seeking. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11121-020-01099-2) contains supplementary material, which is available to authorized users.